참다래 유전체 연구 동향 - 김성철(Seong Cheol Kim); 김호방(Ho Bang Kim); 좌재호(Jae Ho Joa); 송관정(Kwan Jeong Song) (Journal of plant biotechnology, 2015)
Kiwifruit is a new fruit crop that was commercialized in the late 1970s. Recently, its cultivation and consumption have increased rapidly worldwide. Kiwifruit is a dioecious, deciduous, and climbing plant having fruit with hairs and various flesh colors and a variation in ploidy level; however, the industry consists of very simple cultivars or genotypes. The need for efficient cultivar improvement together with the evolutional and biological perspectives based on unique plant characteristics, have recently encouraged genome analysis and bioinformatics application. The draft genome sequence and chloroplast genome sequence of kiwifruit were released in 2013 and 2015, respectively; and gene annotation has been in progress. Recently, transcriptome analysis has shifted from previous ESTs analysis to the RNA-seq platform for intensive exploration of controlled genetic expression and gene discovery involved in fruit ascorbic acid biosynthesis, flesh coloration, maturation, and vine bacterial canker tolerance. For improving conventional breeding efficiency, molecular marker development and genetic linkage map construction have advanced from basic approaches using RFLP, RAPD, and AFLP to the development of NGS-based SSR and SNP markers linked to agronomically important traits and the construction of highly saturated linkage maps. However, genome and transcriptome studies have been limited in Korea. In the near future, kiwifruit genome and transcriptome studies are expected to translate to the practical application of molecular breeding. 키위는 세계적으로 1970년대 이후 상업화되어 최근 재배가 급속히 확대되고 있는 신종 과수이며, 국내에서도 재배와 소비량이 급격히 증가하고 있다. 키위는 자웅이주 낙엽성 덩굴 식물로 과피에 털이 있고 과육색이 다양한 특성을 가지고 있으며 배수성도 다양하나, 산업적인 품종 구성은 매우 단순하다. 독특한 식물적 특성에 기인한 진화 및 생물학적 관점은 물론 다양한 품종의 효율적 개발의 요구에 따라 최근 유전체 해석 및 활용 연구가 활발히 진행되고 있다. 키위 유전체 draft 서열과 엽록체 서열이 Illumina HiSeq 기반으로 각각 2013년과 2015년에 해독 되었으며 gene annotation 연구가 계속적으로 진행되고 있다. 과거 ESTs 기반의 전사체 분석에서 최근 RNA-seq 기반의 전사체 분석으로 전환되어 과일의 아스코르브산 생합성, 과육색 발현 및 성숙, 그리고 나무의 궤양병 저항성 관련 유전적 발현조절과 유전자 발굴 연구가 중점적으로 진행되고 있다. 전통육종의 효율을 증대하기 위한 분자표지 개발 및 유전자지도 작성에 있어서는 이전의 RFLP, RAPD, AFLP 기반의 연구에서 벗어나 NGS 기반의 유전체 및 전사체 정보의 해독에 의한 SSR 및 SNP 기반의 농업적으로 중요한 형질연관 분자마커 개발 및 고밀도 유전자지도 작성이 연구되고 있다. 그러나 국내 연구는 아직 제한적인 수준에서 진행되고 있다. 향후 키위 유전체 및 전사체 분석 연구는 가까운 장래에 실질적으로 분자육종에 적용될 것으로 전망된다.